2015
DOI: 10.1002/mame.201400437
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Behaviors of TRGO-Filled Epoxy Nanocomposites with Different Dispersion/Interface Levels

Abstract: In this work, we investigate mechanical properties and fracture behaviors of thermally reduced graphene oxide (TRGO)-filled epoxy composites with two different dispersion/ interface levels. The amphiphilic surfactant treatment of TRGO was found to promote the dispersion in both water and epoxy, but also produced improved TRGO/epoxy interface. As expected, incorporation of untreated or treated TRGO sheets into epoxy increases the storage modulus and the glass transition temperature. In particular, significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 58 publications
1
27
0
Order By: Relevance
“…It has been observed that the smooth surface of fractured neat epoxy composite was changed to rough surface after the incorporation of single and hybrid fillers. There were small solid lines in the region of cracks, showing brittle nature and low resistance toward propagation of stress fractures [10,13,[44][45][46].…”
Section: Morphologymentioning
confidence: 99%
“…It has been observed that the smooth surface of fractured neat epoxy composite was changed to rough surface after the incorporation of single and hybrid fillers. There were small solid lines in the region of cracks, showing brittle nature and low resistance toward propagation of stress fractures [10,13,[44][45][46].…”
Section: Morphologymentioning
confidence: 99%
“…40,41 In contrast, CNTs and Graphenes have been shown to reinforce through mechanisms like crack bridging behind the crack tip. [42][43][44][45][46] The aspect ratio of CNWs is between that of spherical nanoparticles and carbon nanotubes. This results in the possibility of hybridizing the reinforcement effects from both these types of nanoparticles (promotion of matrix plastic deformation and crack bridging) through the addition of CNWs.…”
Section: Morphological Characterizationmentioning
confidence: 99%
“…However, the thermal transfer properties of graphene‐reinforced epoxy composites can be severely weakened by the agglomeration of graphene, which would result in poor dispersion of graphene in the epoxy matrix and high thermal interface resistance ( R TIM ) in the resulting composites . Therefore, graphene dispersion in an epoxy matrix and interface compatibility between graphene and the epoxy matrix are the key issues for the application of thermally conductive composites …”
Section: Introductionmentioning
confidence: 99%
“…7,8 Therefore, graphene dispersion in an epoxy matrix and interface compatibility between graphene and the epoxy matrix are the key issues for the application of thermally conductive composites. 9,10 Many methods have been attempted to facilitate graphene dispersion in an epoxy (EP) matrix, such as mechanical blending with ultrasonication and high-shear mixing, [11][12][13][14] which was able to break the van der Waals interactions among graphene nanosheets and retain the distinct structure of graphene. However, the enhancement in phonon scattering and mismatch led to a increase in the thermal interface resistance of the resulting composites.…”
Section: Introductionmentioning
confidence: 99%